Suillus placidus Singer, Farlowia 1945 - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Zenodo, 2021)
Suillus placidus (Bonord.) Singer, Farlowia 2 (1): 42 (1945) (Figs. 3 c, d) Pileus 30–100 mm in diam., rounded-convex to plane, viscid to slimy, white, pale-yellow, grey-white, sometimes irregularly colored in brown tints, brown in the center, white on the edges or with brown or grayish stripes or spots. The cuticle is easily removed to the center. Tubes and pores pale-yellow, yellow, from lemon yellow to yellow-brown, adnate or slightly decurrent. Stipe 40–120 mm length, 10–23 mm width, white, yellow in upper part, all covered with small dark-brown glandular dots. Flesh white, slightly yellowish. Smell tarry. Basidia 20–25 × 6–7 μm, cylindrical, clavate, 4-spores. Basidiospores 7–9 × (2.5)3–3.5 μm, Q = 2.0–2.9, fusiform, yellowish-olive. Cheilo - and pleurocystidia 34–52 × 7–12 μm, cylindrical or slightly swollen at the ends, hyaline or with dark-brown content, fasciculate. Pileipellis ixotrichoderm, consisting of intertwined hyphae of 2–7 μm width, immersed in gelatinous substance. Caulocystidia like pleuro- and cheilocystidia, cylindrical, fusiform, clavate, with brown content, fasciculate. Clamp connections absent in all tissues. Ecology and distribution . The species has a Holarctic areal and forms ectomycorrhizae with Pinus : in Europe (Alps)—with Pinus cembra in Siberia and Far East—with P. sibirica , P. koraiensis , P. pumila in India —with P. wallichiana A. B. Jacks (1938: 85); in China —with P. massoniana Lamb. (1803: 12); in North America—with P. strobus (Smith & Thiers 1964; Munoz 2005; Verma & Reddy 2016). In Russia, the species was found in Far East (Vasilyeva 1973), Siberia (Perova & Gorbunova 2001; Zvyagina & Baykalova 2012) and the Urals (Perevedentseva 2008; Palamarchuk 2012; Degteva 2019). It occurs solitary or gregarious. Collection examined . RUSSIA, Troitsko-Pechorsky district, Pechoro-Ilychsky Nature Reserve: the Mountain Medvezhiy Kamen, 62°04’22.3”N, 59°04’39.0”E, spruce green moss forest with Pinus sibirica, 10 Aug. 2004, col. M. Palamarchuk , SYKOf 239; 6 km ...